Tipos de condução de hastes na produção e na qualidade de mini tomate em manejo orgânico - Candian, Joara Secchi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Tomato is an important vegetable crop product, being highly valued by consumers of organic food. Features such as production, size and taste of the fruits can be greatly influenced by plant density that can be increased by reducing the spacing or by increasing the number of stem in each plant. The experiment was conducted in São Manuel-SP between the months of August 2013 on January 2014, with the objective of evaluating the influence of the number of stems per plant and the conduction type in production and physicochemical characteristics of fruits of hybrid Coco tomato, type mini tomatoes. The experiment was conducted in protected cultivation under organic management. The treatments consisted of four different ways of conduction: 2 traditional stems (main stem and stem below the 1st inflorescence); 2 stems coming from axillary buds of cotyledon leaves (named as bottom stem conduction), due to pruning the apical meristem of the plant just above the cotyledons with the seeldlings still in the tray; 3 stems (main stem and two stems side below the 1st and 2nd inflorescences) and 4 stems coming from bottom stem. The fruits were harvested when they wer totally red. It was evaluated total number of fruits per plant, production (g plant -1), earliness production (adding the first four crops) and physico-chemical characteristics (average weight and fruit diameter, pH, titratable acidity, soluble solids, ratio, reducing sugars, ascorbic acid, lycopene, β -carotene, chlorophyll a and b and mass loss (%)) of the fruit. The number and the conduct of the stems did not affect the production of fruits per plant (g plant-1), but with the increase ...

O tomate é um importante produto olerícola, sendo muito valorizado pelos consumidores de alimentos orgânicos. Características como produção, tamanho e sabor dos frutos podem ser bastante influenciados pela densidade de plantio, que pode ser aumentada pela redução do espaçamento ou pelo aumento na quantidade de hastes em cada planta. O experimento foi desenvolvido no município de São Manuel-SP entre os meses de agosto de 2013 a janeiro de 2014, com o objetivo de avaliar a influência do número de hastes por planta e do tipo de condução na produção e nas características físico-químicas dos frutos do tomateiro híbrido Coco, tipo mini tomate. O experimento foi conduzido em cultivo protegido sob manejo orgânico. Os tratamentos consistiram de quatro diferentes formas de condução: 2 hastes tradicionais (haste principal e haste abaixo da 1ª inflorescência); 2 hastes oriundas de gemas axilares das folhas cotiledonares; 3 hastes (haste principal e duas laterais abaixo da 1ª e 2ª inflorescências) e 4 hastes oriundas de poda baixeira. Os frutos foram colhidos quando apresentavam coloração totalmente vermelha. Avaliaram-se o número total de frutos por planta, produção (g planta-1), produção precoce (somando as quatro primeiras colheitas) e características físico-químicas (massa média e diâmetro de frutos, pH, acidez titulável, sólidos solúveis, ratio, açúcares redutores, ácido ascórbico, licopeno, β-caroteno, clorofila a e b e de perda de massa (%)) dos frutos. O número e a condução das hastes não influenciaram a produção de frutos por planta (g planta-1), porém, com o aumento no número de hastes, houve acréscimo no número de frutos por planta, porém com menor diâmetro e massa média. O tratamento com 2 hastes convencionais teve maior produção precoce. Em relação as características físico-químicas dos frutos, o aumento no número de hastes....
Conduction types of stem in production and quality of mini tomato in organic management
Keywords: Tomate - Poda; Produtividade agrícola; Agricultura organica; Físico-química; Tomato products